2021
DOI: 10.1186/s13756-021-00916-9
|View full text |Cite
|
Sign up to set email alerts
|

Expert commentary on the challenges and opportunities for surgical site infection prevention through implementation of evidence-based guidelines in the Asia–Pacific Region

Abstract: Introduction Surgical site infections (SSIs) are a significant source of morbidity and mortality in the Asia–Pacific region (APAC), adversely impacting patient quality of life, fiscal productivity and placing a major economic burden on the country’s healthcare system. This commentary reports the findings of a two-day meeting that was held in Singapore on July 30–31, 2019, where a series of consensus recommendations were developed by an expert panel composed of infection control, surgical and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 64 publications
1
6
0
7
Order By: Relevance
“…To the best of our knowledge, this is the first study to look at both knowledge and attitudes of healthcare professionals on SSI in a study using a pre-test and posttest design. (Anderson et al, 2014;Hegarty et al, 2019;Morikane et al, 2021;Sartelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to look at both knowledge and attitudes of healthcare professionals on SSI in a study using a pre-test and posttest design. (Anderson et al, 2014;Hegarty et al, 2019;Morikane et al, 2021;Sartelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…( 2019 ) also reported that the majority of surgical multidisciplinary staff have positive attitudes towards SSI surveillance and believe that are responsible for the prevention of SSI. Recently, other researchers have concluded that continuous engagement in SSI surveillance as part of a complex intervention at an organisational level improves awareness by clinicians of patient safety and results in better outcomes (Morikane et al., 2021 ; Zucco et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overcoming barriers to evidence-based-practice implementation by promoting compliance with recommended measures, and thus translating evidence into clinical practice, is crucial [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%